Sandwiching saturation number of fullerene graphs - Vesna Andova; František Kardoš; Riste Škrekovski (My University, 2014)
The saturation number of a graph $G$ is the cardinality of any smallest maximal matching of $G$, and it is denoted by $s(G)$. Fullerene graphs are cubic planar graphs with exactly twelve 5-faces; all the other faces are hexagons. They are used to capture the structure of carbon molecules. Here we show that the saturation number of fullerenes on $n$ vertices is essentially $n/3$.
Keywords: Mathematics - Combinatorics; Mathematics - Combinatorics